2017
DOI: 10.1111/jfs.12418
|View full text |Cite
|
Sign up to set email alerts
|

Selection and identification of protective culture for controlling Staphylococcus aureus in fresh Domiati like cheese

Abstract: Antibacterial activity of forty lactic acid bacteria (LAB) isolates toward Staphylococcus aureus was evaluated. The selected strains were then used as protective culture in artificial contaminated Domiati like cheese with S. aureus. The effect of using these strains on physicochemical properties and overall acceptability of fresh cheese was evaluated. Depending on its antibacterial activity, three strains of Lactobacillus rhamnosus 130RZFAAU, 131RZFAAU, and 190RZFAAU were selected for cheese making. No negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This may indicate the ability of both protective cultures to control the growth of S. aureus in Domiati‐like cheese. Similarly, Ibrahim and Awad (2017) reported that three strains of Lactobacillus rhamnosus could suppress the growth of S. aureus in Domiati‐like cheese. S. aureus has a high incidence in Egyptian dairy products particularly in cheeses made from raw milk such as Domiati cheese.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This may indicate the ability of both protective cultures to control the growth of S. aureus in Domiati‐like cheese. Similarly, Ibrahim and Awad (2017) reported that three strains of Lactobacillus rhamnosus could suppress the growth of S. aureus in Domiati‐like cheese. S. aureus has a high incidence in Egyptian dairy products particularly in cheeses made from raw milk such as Domiati cheese.…”
Section: Resultsmentioning
confidence: 88%
“…To circumvent this problem few attempts were directed towards the development of protective culture to improve safety and control S. aureus in Domiati cheese. It has been reported that L. acidophilus La‐5 (El‐Kholy et al, 2014), L. rahmnosus 131RZFAUU (Ibrahim & Awad, 2017), and L. helveticus CNRZ32 (Al‐Gamal et al, 2019) could be successfully used as protective cultures to control the growth of S. aureus in Domiati cheese. Also, application of 1% Lb.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, several authors have performed challenge studies of foodborne pathogens inoculated in milk or cheese to assess the antimicrobial capacity of functional starter cultures or selected LAB (Ibrahim and Awad, 2018;Campagnollo et al, 2018;Atanasova et al, 2014) and plant-based antimicrobials (Artiga-Artigas et al, 2017;Wahba et al, 2010;Menon and Garg, 2001;Tehrani and Sadeghi, 2015;Dannenberg et al, 2016). Thus, a meta-analysis of the published results on the effect of antimicrobial biopreservatives will help evaluate their usefulness to control foodborne pathogens in cheeses (Xavier et al, 2014); and more specifically, compare the effectiveness of the different biopreservatives and modes of application.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions may have a neutral, positive or negative impact on the activity of the strains performing the fermentation (Arioli et al, 2016). Protective cultures have strong antagonistic activity against food-spoilage and pathogenic aerobic spore-forming bacteria as a result of the production of bacteriocins, inhibitory enzymes, organic acids and hydrogen peroxide (Ibrahim and Awad, 2018). Consumers have an increasing knowledge of health risks caused by the usage of chemical preservatives.…”
Section: Introductionmentioning
confidence: 99%